Recent progress in hybrid materials science - Sanchez, Clément; Shea, Kenneth J; Kitagawa, Susumu (Chemical Society reviews, 2011)
This themed issue of Chemical Society Reviews reviews recent progress made in hybrid materials science. Guest editors Clément Sanchez, Susumu Kitagawa and Ken Shea introduce the issue and the academic and industrial importance of the field.